Parameters Affecting Length of Stay Among Neurosurgical Patients in an Intensive Care Unit - Phuping Akavipat (Acta Medica Indonesiana, 2017)
Aim: to determine the predictive factors on the length of stay of neurosurgical patients in the ICU setting. Methods: all patients admitted to the neurosurgical ICU between February 1 and July 31, 2011 were recruited. Patient demographics and clinical data for each variable were collected within 30 minutes of admission. The ICU length of stay was recorded and analyzed by linear regression model with statistical significance at p-value <0.05. Results: there were 276 patients admitted, of whom 89.1% were elective cases. The mean (95% CI) and median (min-max) of ICU length of stay were 2.36 (2.09-2.63) and 2 (1-25) days. The variables associated with ICU length of stay and their percent change (95% CI) were the Glasgow Coma Scale motor subscore (GCSm), 6.72% (-11.20 to -2.01) lower for every 1 point score change; blood pH, 1.16% (0.11 to 2.21) higher for every 0.01 unit change; and emergency admission type, 58.30% (29.16 to 94.0) higher as compared to elective admission. Conclusion: the GCSm, pH and emergency admission were found to be the main predictive variables of neurosurgical patient length of stay in the intensive care unit, however, the model should be further explored in a larger sample size and using subgroup analysis.